2022
DOI: 10.1039/d1ma01071a
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic nanocarriers adorned on graphene: promising contrast-enhancing agents with state-of-the-art performance in magnetic resonance imaging (MRI) and theranostics

Abstract: Magnetic Resonance Imaging (MRI) is an effectual imaging technique for medical diagnosis, its non-invasive nature being a noteworthy attribute, where magnetic contrast agents are employed to improve sensitivity and accuracy....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 125 publications
0
13
0
Order By: Relevance
“…Magnetic NPs (MNPs) have been studied as MRI nanoscale contrast agents and MNP-based targeted drug delivery for targeted cancer therapeutic and diagnostic applications, acting at the cellular and molecular levels due to their unique physicochemical characteristics . MNPs can be fabricated from cobalt metals, iron, as well as various cobalt alloys and iron oxides.…”
Section: Advanced Nanosystems For Targeted Cancer Therapeuticsmentioning
confidence: 99%
“…Magnetic NPs (MNPs) have been studied as MRI nanoscale contrast agents and MNP-based targeted drug delivery for targeted cancer therapeutic and diagnostic applications, acting at the cellular and molecular levels due to their unique physicochemical characteristics . MNPs can be fabricated from cobalt metals, iron, as well as various cobalt alloys and iron oxides.…”
Section: Advanced Nanosystems For Targeted Cancer Therapeuticsmentioning
confidence: 99%
“…Graphene-related nanomaterial magnetic composites have a great advantage in helping these imaging guided therapy processes to improve the signals or contrasts to provide enhanced resolution in the final images during disease identification [ 99 ]. GO has been a scaffold for many imaging probes and drug loadings, and there are several works that have discussed magnetic nanoparticles-loaded GO, creating a better contrast agent due to its high loading capacity [ 100 ]. Recently, the oxidation of ball-milled graphite producing a nanoGO was reported.…”
Section: Graphene Nanocomposite Theranostics For Multimodal Imaging G...mentioning
confidence: 99%
“…In brief, many authors have reported that GO- and RGO-based iron oxide nanocomposites are excellent for MR imaging and guided therapy of cancer [ 100 ]. As discussed earlier, we also prepared an MFG-SiNC 4 with excellent superperamagnetic properties, fluorescence, biocompatibility, and water dispersability for in vitro MRI to serve as a good contrast agent, as shown in Figure 6 A,B.…”
Section: Graphene Nanocomposite Theranostics For Multimodal Imaging G...mentioning
confidence: 99%
“…Metal−organic frameworks (MOFs), which consist of metal nodes and bridging ligands, are regarded as a kind of promising and tunable supports for different active sites to construct multifunctional catalysts because of their thermal/chemical stability, 11,17−20 adjustable porous frameworks, well-defined structures, 21,22 high density of uniformed catalytic sites, and crystalline nature for easily elucidating structure−function relationships. 23−25 Numerous MOF-based heterogeneous catalysts have been successfully synthesized and reported in the past decade via precisely introducing programmed catalytic sites into their frameworks.…”
Section: Introductionmentioning
confidence: 99%